2023
DOI: 10.1111/1471-0528.17402
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal complications following Kielland's rotational forceps delivery: A systematic review and meta‐analysis

Abstract: Malposition in labour is a term used to describe a fetus in a cephalic presentation with the fetal occiput in a transverse (OT) or posterior (OP) position, in relation to the maternal spine. 1 If the position remains OT or OP at the end of the active phase of the second stage of labour, persistent fetal malposition (PFM) is diagnosed. There are essentially four management options for PFM: Kielland's rotational forceps delivery (KFRD); rotational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Positional care during delivery is a method of correcting abnormal fetal orientation based on the changes in fetal position during different stages of labor, by guiding the mother to adopt correct positions to promote smooth labor [7]. Compared to the other two methods of promoting fetal head rotation, instrumental rotation and manual rotation, positional care, may be associated with less fetal and maternal complications, making it more popular for the midwife [8,9]. Doulas were first mentioned in a study about the effect of a supportive companion of perinatal women published in 1980 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Positional care during delivery is a method of correcting abnormal fetal orientation based on the changes in fetal position during different stages of labor, by guiding the mother to adopt correct positions to promote smooth labor [7]. Compared to the other two methods of promoting fetal head rotation, instrumental rotation and manual rotation, positional care, may be associated with less fetal and maternal complications, making it more popular for the midwife [8,9]. Doulas were first mentioned in a study about the effect of a supportive companion of perinatal women published in 1980 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Dr Papageorghiou, Matsubara et al 1 posed the question if Kielland's forceps are for the exclusive use of doctors from the UK following a recent meta-analysis by Giacchino et al 2 . This meta-analysis found that Kielland's forceps are safe for the management of malposition of the fetal head in the second stage of labour.…”
mentioning
confidence: 99%